2018
DOI: 10.1016/j.ajog.2018.09.039
|View full text |Cite
|
Sign up to set email alerts
|

A US population-based study of uterine fibroid diagnosis incidence, trends, and prevalence: 2005 through 2014

Abstract: BACKGROUND: Despite considerable public health burden, uterine fibroid population-based incidence estimates are few. Secular trends over time are even more limited. OBJECTIVE: We sought to evaluate the incidence, 10-year secular trends, and prevalence of uterine fibroid diagnoses and describe the proportion of symptomatic women. STUDY DESIGN: We performed a retrospective population-based cohort study of women, aged 18e65 years, enrolled 2005 through 2014 in Kaiser Permanente Washington. Uterine fibroid diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
(24 reference statements)
5
31
0
1
Order By: Relevance
“…The KPWA population generally reflects the underlying community it serves with respect to age, race, and sex. 10 The cohort consisted of all women aged 16e60 years in 2006e2015 enrolled at KPWA for a minimum of 2 years with at least 1 health care utilization at KPWA in the 2 years before cohort entry on January 1, 2006, through December 31, 2015. We further restricted to women who did not have a record of hysterectomy at least 61 days (or 2 months) prior to cohort entry.…”
Section: Study Setting and Cohortmentioning
confidence: 99%
“…The KPWA population generally reflects the underlying community it serves with respect to age, race, and sex. 10 The cohort consisted of all women aged 16e60 years in 2006e2015 enrolled at KPWA for a minimum of 2 years with at least 1 health care utilization at KPWA in the 2 years before cohort entry on January 1, 2006, through December 31, 2015. We further restricted to women who did not have a record of hysterectomy at least 61 days (or 2 months) prior to cohort entry.…”
Section: Study Setting and Cohortmentioning
confidence: 99%
“…The prevalence is known to increase with age, especially among women aged 50–54 years (15.9%). 1 UFs usually result in a series of chronic symptoms, such as heavy menstrual bleeding, pelvic pain and bladder dysfunction. In addition, UFs may cause reproductive problems including infertility and pregnancy complications.…”
Section: Introductionmentioning
confidence: 99%
“…Smooth muscle tumors of the uterus are extremely common while the HLRCC syndrome is uncommon. A US population‐based study of uterine fibroids showed an overall prevalence of 9.6%, and a 15.9% prevalence among 50 to 54‐year‐old women 17 . The true prevalence of HLRCC is not known; it is estimated to affect roughly 1 in 200 000 individuals and has been reported in approximately 300 families worldwide, but it is likely underdiagnosed.…”
Section: Introductionmentioning
confidence: 99%